Predicting Subjective Well-Being Based on Psychological Capital Mediated by Agency in Homemakers in Tehran - Rastegar, Mansoureh; Basri, Ahmad (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The aim of the present study was to identify the extent to which psychological capital influences subjective well-being through the mediating role of agency among homemakers in Tehran.Methods and Materials: The research design was applied in terms of purpose and descriptive-correlational in terms of data collection method. The statistical population included all homemakers aged 20 to 50 in Tehran. A sample size of 200 participants was selected using multistage random sampling from Districts 14 and 15 of Tehran. The research instruments included the Subjective Well-Being Questionnaire by Diener et al. (1985), the Agency Questionnaire by Tapal (2017), and the Psychological Capital Questionnaire by Luthans and Avolio (2007).Findings: The results indicated that the subjective well-being of homemakers can be predicted based on psychological capital (p < .01). Furthermore, agency was found to significantly mediate the relationship between psychological capital and subjective well-being (p < .01).Conclusion: Based on the above findings, it can be concluded that enhancing subjective well-being in homemakers can be achieved both directly by increasing psychological capital and indirectly through the enhancement of agency. As psychological capital and agency increase, individuals’ levels of subjective well-being also improve.